MODEL PEMBELAJARAN TASK BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN MEMBACA TEKS BERBAHASA INGGRIS SISWA - Dermawati Dermawati (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2021)
This Class Action research was conducted to look at students' improved reading skills through interesting and varied reading materials and the design of diverse reading tasks in English subjects and found the obstacles they faced in improving their reading skills. This research was conducted on students of class XII IPS1 SMA N I Kecamatan Kapur IX, Kabupaten Lima Puluh Kota. The research was conducted in two cycles. Data is obtained through pre-test results, observation sheets, field records, fill formats, and post-tests.  The results of each cycle are analyzed both in terms of process and repeat/test results. In terms of the process can be observed from the enthusiasm of students in answering questions both oral and written accurately. In terms of results, judging from the results of the replay carried out at the end of each cycle. Furthermore, the results of each cycle analysis are used as a reference for the learning of the next cycle. Through observations, questionnaires, test results every cycle, and post-tests, the results of this study show students enjoy reading learning and there is an increase in their abilities. Learning to read in English will be more successful if the teacher uses interesting readings, tasks that vary in delivering the material. For that, the teacher must be more active in preparing manuscripts - varied English scripts and challenging tasks.